Regional Public Policy and Tourism Life Cycle: the Case of Sardinia - Bianca Biagi; Manuela Pulina (European Regional Science Association (ERSA), 2006)
The life cycle approach (LCA) is considered as a useful prescriptive and normative tool for analysing the development of destinations and evolution of markets. A case study of the Island of Sardinia (Italy) highlights the utility of the LCA approach because this region provides a long run indicator, in terms of nights of stay, number of beds and accommodation for approximately eighty years of tourism activity and, throughout this time span, the Island has experienced several stages of the life cycle. One of the aims of this paper is to verify the lag between tourist consumption and tourist production. An econometric and descriptive approach has detected heterogeneities between the domestic and international tourist life cycle. The main result is that in recent years Sardinian tourism has experienced a decline stage of the domestic demand and a maturity stage for the international demand, while the supply is still in the growth phase. Moreover, the paper shows that the dynamics of tourist demand are strictly dependent on the local public policy makers' actions and socio-economic changes. Furthermore, the development of the accommodation sector is triggered by different factors as well as the tourist demand. In the last few years numerous changes have occurred in Sardinia in terms of transportation (e.g. low cost airlines), progress in information technology and public policy, that have influenced the preferences of tourists; nevertheless, the divergence between demand and supply within the life cycle framework introduces three main critical areas to be addressed: the importance of a long run economic planning; the sustainability of tourism production; and the role of market information for tourist operators.
Keywords: 330